Longitudinal Contributions of Phonemic Awareness to Reading Greek Beyond Estimation of Verbal Ability and Morphological Awareness. Issue 3 (4th May 2018) - Pittas, Evdokia
ABSTRACT: This longitudinal study considers the contributions of language awareness to children's learning to read and spell. The aim of the study was to examine whether the connection between phonemic awareness and literacy in Greek is constant over time even when appropriate controls are taken into account. I examined this hypothesis with Greek Cypriot children ( N  = 404) ages 6 to 10. Results showed that after an interval of 8 months and even after I controlled for the estimation of verbal ability and morphological awareness, phonemic awareness predicted children's performance in reading. Phonemic awareness predicted spelling only after I controlled for the estimation of verbal ability. In terms of the need to establish more general theories about phonemic awareness and literacy, this study contributes the long-term relation between phonemic awareness and literacy in Greek. In practice, this study contributes valid measures for assessing phonemic and morphological awareness in Greek.